MANAJEMEN KEWIRAUSAHAAN UNTUK MENINGKATKAN USAHA KESEHATAN SEKOLAH DI SLB KABUPATEN BANDUNG BARAT - sukmatiniawati, reni (Wali Pikir: Journal Of Education, 2023)
Indonesia is vigorously implementing a healthy community movement and participate in efforts to improve the hygiene and health of Indonesia's population that has the largest population of 46.497.175 million people, due to the fact Indonesia's health profile according to expert health experts in 2010 the average households with category of Clean and Healthy Behavior (PHBS) reached 35.68%. The spearhead of health development for the community through counseling in , health services in schools through the Government's attention to the movement of healthy Society, especially to further optimize School Health Enterprises in Public School expected to be improved, not least in Special School. Implementation of UKS in Special Education  Schools certainly requires good management along with the complexity of learners in the Special Education Schools Heterogene type of abnormality (Blind, Deaf, Mental Retardation, Autism, disability, social behavior and Double Handycape), the needs of each level of education from the basic level to the level medium. The management of learning in Special Needs Education  the implementation of the UKS program requires entrepreneurial spirit from the principal who is very objective and specific, especially in preparing the program, implement it. The entrepreneurial spirit is built with innovation, working hard, cooperating with related parties such as Puskesmas, Medical team and health experts to UKS program in Special Education schools  done and implemented in the Implementation Plan both individual and classical learning. The management of entrepreneurship in West Bandung Special School to improve School Health Enterprises is expected to be a change agent in providing the teaching resources of students in Special Needs Education so as to reduce the number of morbidity, acquire health knowledge, implementing Clean and Healthy Behavior in daily life, although still with the guidance of teachers and parents should be done gradually and continuously so that the community environment can accept their existence without feeling awkward.